Renaissance and Baroque art and culture in the Eastern Polish-Lithuanian Commonwealth (1506-1696) - Szulakowska, Urszula (Cambridge Scholars Publishing, 2018)
This monograph serves as an introduction to the art, architecture and literary culture of the Eastern Polish-Lithuanian Commonwealth in the 16th and 17th centuries. The geographical area under discussion comprises the regions of contemporary Lithuania, western Belarus and western Ukraine. The introduction of the Renaissance and Baroque classical revival into these lands is considered here within the political context of nationalistic and religious loyalties, as well as economic status and class. The central discussion focuses on the issue of national identity and religious loyalty in the inter-relation between the Byzantine inheritance of the Lithuanian and Ruthenian populace and the Polonizing Catholic influences entering from the west. A close study is made of the royal, noble and urban patronage of the richly-diverse visual and literary modes developed in these two centuries, as well as examining the cultural achievements of the many national groups in the Eastern Commonwealth, including Ruthenians, Lithuanians, Poles, Armenians, Jews, Karaite and Islamic Tatars. A major issue explored here is the problem of restoring and conserving the vast amount of devastated material culture in these regions, particularly in Belarus.